Efektivitas Senam Iringan Gamelan Terhadap Tekanan Darah Lansia Dengan Hipertensi - Margiyati Margiyati; Novita Wulansari (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Background: Hypertension is a cardiovascular disease that attacks many elderly people and increases the risk of death. The aging process causes elderly people to decrease their activity, resulting in the emergence of obesity, fat accumulation in blood vessels, and increased blood pressure. Data in the area supported by the Srondol Semarang Community Health Center in 2020 shows that hypertension is in first place on the list of the top 10 diseases there. One intervention that is safe and popular with the elderly and can help control blood pressure in the elderly is gamelan accompaniment exercise because it can increase blood flow and oxygen supply throughout the body, increase the elasticity of blood vessels and provide a relaxing effect. The aim of this study was to determine the effectiveness of gamelan accompaniment to blood pressure in elderly people with hypertension. This research method is a pre-experimental one group pre and post test design and sampling using purposive sampling technique. The population of this study were elderly people who were recorded as suffering from hypertension at the Srondol Semarang Community Health Center. The research instrument used a digital spygmomanometer and video of gamelan accompaniment of exercises. The research stages consist of preparation, implementation and processing of research data. The steps taken at the preparation stage were literature studies, field surveys, discussions with lecturers and experts, developing procedures for implementing gamelan accompaniment exercises, expert reviews, and socializing the implementation of gamelan accompaniment exercises to the elderly and their families. The implementation stage was carried out by collecting data on elderly people registered at the Srondol Semarang Community Health Center, pre and post tests by measuring blood pressure using a spigmomanometer, implementing gamelan accompaniment exercises in accordance with the prepared SOP, observing the implementation of gamelan accompaniment exercises with an observation sheet. Then, at the data processing stage, a test was carried out on the effectiveness of gamelan accompaniment exercises on the blood pressure of elderly people with hypertension. The targeted output is publication in national journals indexed by Sinta and HAKI. The TKT target for implementing this gamelan accompaniment exercise is at level 2. The results of the study show a significant reduction in systolic and diastolic blood pressure (p value 0.0001) with an error level (α) of 0.05, namely from 163.25 mmHg to 146.75 mmHg and from 100 .50 mmHg to 89.25 mmHg. Gamelan accompaniment exercises were concluded to be effective in lowering blood pressure in elderly people with hypertension